Inovasi Pendidikan Karakter di Era Milenium Melalui Strategi The Nine Golden Habitsdi SMP Unismuh Makassar - Amirah Mawardi; Nurhidaya M; Maria Ulviani; Alamsyah Alamsyah (UMSU, 2020)
This study uses a learning culture study approach. The type of research method used is qualitative-descriptive. The techniques used in data collection are: 1) observation. 2) Interview. 3) Documentation or records. The conclusion of this research is there is a character education innovation program at SMP Unismuh Makassar, the name of the program is The Nine Golden Habits, where every habit has implications, namely Habit 1: The habit of praying must be on time at the beginning of time and in congregation has implications for the mental of obedient students and love to Allah's orders. Habit 2: The habit of fasting sunnah Monday-Thursday, imposes an impact on the honesty and self-control of students. Habit 3: The habit of giving and giving alms has implications for the change of an attitude of social concern and empathy for others. Habit 4: The habit of reading the Al-Qur'an, it has implications for the tradition of reciting the Koran and self-reflection in improving the laws of reading. Habit 5: Islamic habitation, this habit implies the growth of the habit of being polite and courteous to teachers and other students. Habit 6: Scheduled reading habits, implicating students' habits to actively seek knowledge and broad horizons. Habit 7: The habit of following recitation and study has implications for students' habits to deepen their religious knowledge and enjoy being in recitation sessions. Habit 8: Habitual organization, which implies that students are accustomed to collaborating, are responsible and having leadership skills. 9: Habit of positive thinking, this habit has implication for the habit of prejudice.